2021
DOI: 10.3390/cells10081869
|View full text |Cite
|
Sign up to set email alerts
|

HDL in Atherosclerotic Cardiovascular Disease: In Search of a Role

Abstract: For a long time, high-density lipoprotein cholesterol (HDL-C) has been regarded as a cardiovascular disease (CVD) protective factor. Recently, several epidemiological studies, while confirming low plasma levels of HDL-C as an established predictive biomarker for atherosclerotic CVD, indicated that not only people at the lowest levels but also those with high HDL-C levels are at increased risk of cardiovascular (CV) mortality. This “U-shaped” association has further fueled the discussion on the pathophysiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(32 citation statements)
references
References 130 publications
0
16
0
Order By: Relevance
“…A worldwide study demonstrated that among all modifiable risk factors of CV disease, abnormal serum levels of cholesterol were associated with the highest attributable risk for the occurrence of CVD, especially ischemic heart disease [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…A worldwide study demonstrated that among all modifiable risk factors of CV disease, abnormal serum levels of cholesterol were associated with the highest attributable risk for the occurrence of CVD, especially ischemic heart disease [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…An explanation for this may be the effect of HDL-C, as has been described. Previous studies have also found a U-shaped association which has further fueled the discussion on the pathophysiological role of HDL in cardiovascular diseases [ 36 ]. This may mean that a single assessment method for CVD risk using HDL-C is unsuitable.…”
Section: Discussionmentioning
confidence: 90%
“…HDL-C level has been challenged time and time again for its association with cardiovascular diseases. Instead, the HDL function may be the real link with cardiovascular diseases [ 29 ]. Since the role of HDL in prevention and progression of cardiovascular diseases remains to be further clarified, we assume, in the current study, that extremely low level of HDL-C is only a marker, which reflects a comprehensive result of multiple adverse concomitant factors, and the high cardiovascular mortality is probably due to the presence of severe conditions.…”
Section: Discussionmentioning
confidence: 99%